2016
DOI: 10.1002/btpr.2312
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and optimizing the addition of phytohormones in the culture of microalgae for lipid production

Abstract: Some studies have described the use of phytohormones in microalgal culture for the production of biodiesel or selected fatty acids. However, no study has determined the amount of phytohormones that maximizes lipid yield. We determined the optimal concentration of auxins and gibberellins (which is between 40 and 60 μM) in two strains (Scenedemus abundans and Chlorella ellipsoidea) suitable for biodiesel production. More than 3-fold increment was reached with S. abundans and near 7-fold increment with C. ellipso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Our results are consistent with those of a previous report detailing the responses of Scenedesmus abundans and Chlorella ellipsoidea to 2,4-dichlorophenoxyacetic acid (2,4-D) and/or gibberellic acid (GA3) addition [9]. The improved growth of the microalgae in the presence of phytohormones is likely due to a reduction in the level of cellular reactive oxygen species (ROS), whereas high concentrations of phytohormones may behave as herbicides [9].
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with those of a previous report detailing the responses of Scenedesmus abundans and Chlorella ellipsoidea to 2,4-dichlorophenoxyacetic acid (2,4-D) and/or gibberellic acid (GA3) addition [9]. The improved growth of the microalgae in the presence of phytohormones is likely due to a reduction in the level of cellular reactive oxygen species (ROS), whereas high concentrations of phytohormones may behave as herbicides [9].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Phytohormones are derived from plants and affect plant growth and metabolism [9, 10]. Phytohormones, including auxin, auxinabscisic acid (ABA), cytokinin (CK), ethylene (ET), gibberellins (GAs) and 5-Aminolevulinic acid (5-ALA), have been detected in a variety of microalgal lineages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falkowska et al (2011) also showed GA3 had a stimulating influence on the cell number in C. vulgaris. Similarly, it was observed that GA treatment increased biomass productivity by 8.7-fold and 5.3-fold, respectively, in C. ellipsoidea and Scenedesmus abundans (González-Garcinuño et al, 2016). In this study, microscopic analysis in the present study showed that application of GA3 significantly affected cell size in C. vulgaris culture (Table 1).…”
Section: Effect Of Gibberellin On Cell Growth and Sizesupporting
confidence: 79%
“…However, this strategy incurs additional costs and suffers from contamination issues since it involves the supplementation of organic substrates such as glucose, acetate, glycerol, etc. [60,62,[66][67][68].…”
Section: Addressing Bottlenecksmentioning
confidence: 99%